Market Concentration, Market Shares, and Retail Food Prices: Evidence from the U.S. Women, Infants, and Children Program. (30th August 2018) - Ma, Meilin; Saitone, Tina L.; Volpe, Richard J.; Sexton, Richard J.; Saksena, Michelle
Abstract: We explore pricing in local food‐retailing markets where supermarkets operate versus those occupied solely by smaller food retailers. Using data from the Women, Infants, and Children program in the Greater Los Angeles area, we show that supermarkets do not raise prices in local markets or as a function of market concentration or firm market shares. Smaller food retailers charge substantially higher prices on average than supermarkets. Their prices increase with market concentration and shares of sales, especially when small retailers face no direct competition from supermarkets. Given the dominance of small retailers in some low‐income areas, our findings have important implications regarding local market power, food costs, and supermarket entry.